Diversity of the genus Sheathia (Batrachospermales, Rhodophyta) in northeast India and east Nepal - Necchi, Orlando [UNESP]; West, John A.; Ganesan, E. K.; Yasmin, Farishta; Rai, Shiva Kumar; Rossignolo, Natalia L. [UNESP] (Korean Soc Phycology, 2019)
Freshwater red algae of the order Batrachospermales are poorly studied in India and Nepal, especially on a molecular basis. During a survey in northeast India and east Nepal, six populations of the genus Sheathia were found and analyzed using molecular and morphological evidence. Phylogenetic analyses based on the rbcL gene sequences grouped all populations in a large Glade including our S. arcuata specimens and others from several regions. Sheathia arcuata represents a species complex with a high sequence divergence and several smaller clades. Samples from India and Nepal were grouped in three distinct clades with high support and representing new cryptic species: a Glade formed by two samples from India, which was named Sheathia assamica sp. nov.; one sample from India and one from Nepal formed another Glade, named Sheathia indonepalensis sp. nov.; two samples from Nepal grouped with sequences from Hawaii and Indonesia (only 'Chantransia' stages) and gametophytes from Taiwan, named Sheathia dispersa sp. nov. Morphological characters of the specimens from these three species overlap one another and with the general circumscription of S. arcuata, which lacks the heterocortication (presence of bulbous cells in the cortical filaments) present in other species of the genus Sheathia. Although the region sampled is relatively restricted, the genetic diversity among specimens of these three groups was high and not closely related in the phylogenetic relationship with the other clades of S. arcuata. These data corroborate information from other groups of organisms (e.g., land and aquatic plants) that indicates this region (Eastern Himalaya) as a hotspot of biodiversity.
Keywords: biodiversity; Eastern Himalaya; freshwater Rhodophyta; molecular systematics; morphometrics; rbcL